Origins and process of forming the colloquial idioms – guan yong yu in Chinese. - Kerimbaev., E. A. (Journal of Oriental Studies, 2016)
The article describes the sources and development of one of the main phraseological units in the Chinese colloquial idioms-guan yung yu.